Effectiveness of Virtual Reality in the Motivational Processes of Learners - North, Sarah M. (International Journal of Virtual Reality, 1996)
This brief article reports on the use of virtual reality and its effectiveness on improving and maintaining learners' intrinsic motivation or interest. Research suggests that interest contributes to learning. Therefore a study of the impact of interests is essential to an understanding of intrinsic motivation. Since the virtual environment provides a sense of presence, it may be possible to create scenarios to stimulate the learners' curiosity and interest. Eighteen students, 11 males and 7 females, between 21 and 32 years old, served as subjects for the study. The experiment consisted of the physical world environment using wooden blocks, and the virtual world using virtual blocks. Both worlds used color and shape as variables. The two variables consisted of three shapes (sphere, pyramid, and cube), and three colors (red, green, and blue). In both worlds, the wooden blocks and virtual blocks had to be manipulated and arranged in nine different patterns. The first experiment started with a two-block pattern. At each step the difficulty was increased by increasing the number of blocks. The subject's score was based on a ten-point scale instrument administered at the end of each experiment. The scores ranged from very weak to very strong. The results were used to identify a significant difference between the subjects' performance in the virtual world and in physical world with respect to curiosity, interest, and sense of control. The interest level comparison indicated that for all subjects scores in the virtual world were always higher than the scores in the physical world. The sense of control level comparison indicated that in the beginning scores in the virtualworld were not always higher than the scores in the physical world. However, after orientation to navigation through the virtual environment, the mean score gradually rose. This research demonstrates that the virtual world is more useful than the physical world (with respect of color and shape) in increasing the memory span of the learner.